PENGEMBANGAN SISTEM INFORMASI RESERVASI DAN CUSTOMER RELATION MANAGEMENT PADA RESTORAN 3 WISE MONKEYS - Laurentia Anggun P; Kristina G. Simanjuntak; Kusno Prasetya; Andree E. Widjaja (Jurnal Ilmiah Matrik, 2019)
The current competitions between businesses is getting more intense, one of those competitions is in restaurant business. 3 Wise Monkeys is a restaurant that is trying to improve its customer service. One of the main problems is the unavailability of tables when they come to the restaurant, whcih can affects customer’s judgement. This research aims to help the customer and restaurant owner by designing an online reservation system to book the table and food. The benefit of the system for the customer is that they can choose their table and the menu even before they arrive to the restaurant. Furthermore, there is doorprize feature for the customers who make online reservatoin, making them want to come back in the future and use the online system. The benefit for the restaurant owner is the system can produce informations regarding the number of members, what is the favorite menus, and what time is the busiest hour for the restaurant